Genome-wide association analysis in identification of superior haplotypes for vegetative stage drought stress tolerance in rice - Nayak, Gyanisha; Parameswaran, C.; Vaidya, Nairita; Parida, Madhuchhanda; Sabarinathan, S.; Chaudhari, Prabharani; Sinha, Pallavi; Singh, Vikas Kumar; Samantaray, Sanghamitra; Katara, Jawahar Lal (Springer, 2025)
Water availability is the most critical factor limiting rice yield in rainfed agro-ecosystems. Drought stress during the vegetative stage inhibits key growth processes, such as leaf formation and tillering, significantly impacting yield. This study aimed to investigate the genetic basis of vegetative stage drought tolerance and identify QTLs and genes associated with it through GWAS. A total of 19 major QTLs were identified for six traits: leaf rolling, relative water content, plant height, leaf area, tiller number, and leaf number, with phenotypic variances ranging from 10.55 to 80.05%. Additionally, haplotypes for six candidate genes were identified: OsCYP72A32 for leaf rolling, OsNCX5.2 for relative water content, OsSPX2 for plant height, OsSTA104 for tiller number, OsRING313 for leaf number and Os3BGlu6 for leaf area. Besides, genotypes such as NCS 901 A, H 15-23-DA, LOHAMBITRO and MEJANES 2 were found to be superior donors. These tolerant genotypes and superior haplotypes can be used in haplotype-based breeding programs to enhance drought tolerance in rice at vegetative stage.